2015
DOI: 10.1200/jop.2014.001438
|View full text |Cite
|
Sign up to set email alerts
|

Improving Incidence of Code Status Documentation Through Process and Discipline

Abstract: Documentation of a patient's preferred code status is a critical outcome of advance care planning. Although there is agreement that code status is valuable information, little progress has been made to increase the incidence of documented code status within the medical record in an outpatient setting. Incidence of code status documentation in the community oncology setting has not been studied. In April 2013, the US Oncology Network and McKesson Specialty Health launched a new advance care planning initiative … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0

Year Published

2017
2017
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(16 citation statements)
references
References 8 publications
0
16
0
Order By: Relevance
“…22 In another US Oncology study, Neubauer and colleagues reported that the implementation of an ACP process at 38 member sites resulted in a 15.6% increase in the incidence of code status documentation, and although the incidence of documentation varied considerably, it was as high as 89% at some sites. 23 …”
Section: Discussionmentioning
confidence: 99%
“…22 In another US Oncology study, Neubauer and colleagues reported that the implementation of an ACP process at 38 member sites resulted in a 15.6% increase in the incidence of code status documentation, and although the incidence of documentation varied considerably, it was as high as 89% at some sites. 23 …”
Section: Discussionmentioning
confidence: 99%
“…In addition, a targeted approach to identifying patients who qualify for acp discussions has been shown to increase uptake in patients who engage in acp discussions 17 . Studies have shown that various strategies, including identifying patients from health records 18 , providing electronic prompts for physicians 19 , and educating staff and regularly reporting results 17,18 can increase the rate of goc documentation.…”
Section: Scope Of the Problemmentioning
confidence: 99%
“…11 Electronic prompts within EHR systems for AD documentation updates at the time of care encounters have been shown to increase code status documentation within medical records. [12][13][14] A recent systematic review identified automated prompts, documentation prompts, and electronic order sets as the most common EHR tools reported to improve ACP documentation. 15 Communication regarding goals of care is essential and should be enhanced with EHR, not hindered by EHR.…”
Section: Case Report Perspectivementioning
confidence: 99%